2018
DOI: 10.1007/s10529-018-2577-5
|View full text |Cite
|
Sign up to set email alerts
|

UHRF2 promotes DNA damage response by decreasing p21 via RING finger domain

Abstract: UHRF2 may negatively modulate p21 to regulate DNA damage response, suggesting a novel pathway of UHRF2 repairing DNA damage through the partial regulation of p21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Through cooperative DNA and histone binding, it may contribute to tighter epigenetic control of the gene expression in differentiated cells. Recent research found that UHRF2 can promote the DNA damage response (Wang et al, 2018). The gene DNAJC6 belongs to the evolutionarily conserved DNAJ/HSP40 family of proteins, which regulate the molecular chaperone activity by stimulating the ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Through cooperative DNA and histone binding, it may contribute to tighter epigenetic control of the gene expression in differentiated cells. Recent research found that UHRF2 can promote the DNA damage response (Wang et al, 2018). The gene DNAJC6 belongs to the evolutionarily conserved DNAJ/HSP40 family of proteins, which regulate the molecular chaperone activity by stimulating the ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above four E3 ubiquitin ligases, other proteins can regulate the degradation process of p21. For example, five E3 ubiquitin ligases (UHRF2 [ 33 ], UBR5 [ 34 ], SOCS1 [ 35 ], COPA3 [ 36 ] and ZNF313 [ 26 , 37 ]) and two deubiquitylases (USP11 [ 38 ] and USP36 [ 39 ]) have been reported to mediate p21 stability. In our work, we investigated four most frequently E3 ligases, especially SKP2.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degradation of p21 mediated by human CRL2 LRR1 complex does not appreciably affect cell cycle progression [ 190 ]. Up to date, ZNF313 [ 191 ], RNF126 [ 192 ], CHIP [ 193 ], CRL4B DCAF11 [ 194 ], UHRF2 [ 195 ], SPSB1 [ 196 ], NEDD4 [ 197 ], and FBXO22 [ 198 ] have also been added to the growing list of E3 ubiquitin ligases that control the abundance of p21 protein. Compared with the ubiquitination studies of p21, the identified deubiquitinases targeting p21 are much less.…”
Section: Ubiquitination and Deubiquitination Involved In Ckismentioning
confidence: 99%